Clinical outcome prediction of Contour Neurovascular System treatment based on pre-treatment geometric and hemodynamic characteristics - Fina Gießler; Anna Bernovskis; Franziska Gaidzik; Jana Korte; Philipp Berg; Sönke Peters; Naomi Larsen; Sylvia Saalfeld (International Journal of Computer Assisted Radiology and Surgery, 2026)
Abstract Purpose The contour neurovascular system (CNS) is increasingly used for endovascular treatment of intracranial aneurysms, but outcome and post-treatment device behavior vary between patients. This study investigated whether pre-treatment geometric and hemodynamic characteristics from image-based blood flow simulations are associated with clinical outcome and follow-up CNS shape modifications. Methods Pre-treatment vascular geometries and blood flow simulations were analyzed in 39 CNS-treated cases. Geometric, hemodynamic, and ostium-flow clustering features were extracted, followed by global feature thinning to reduce redundancy. Associations with binary clinical outcome and follow-up shape modifications (SM1–SM3) were assessed using nonparametric univariate statistics with false discovery rate correction. Exploratory outcome discrimination was evaluated using a support vector machine classifier. Results Aneurysm geometry showed the strongest association with clinical outcome. Smaller dome and ostium areas were associated with positive outcome (Cliff’s δ = − 0.57 and − 0.43), while hemodynamic parameters showed weaker but directionally consistent trends, including lower peak outflow velocity, and reduced inflow intensity. Shape-modification patterns differed across deformation classes. SM1 and SM2 showed no FDR-significant features but moderate effects for aneurysm geometry and selected hemodynamic metrics. SM3 showed the strongest associations with oscillatory flow characteristics ( δ ≈ 0.56–0.57) and peripheral outflow dominance. Exploratory machine learning showed limited, non-significant outcome discrimination (mean AUC = 0.57), with selected features consistent with univariate findings. Conclusion Pre-treatment geometric and hemodynamic characteristics are linked not only to clinical outcome but also to post-treatment CNS shape modifications. By linking pre-operative flow conditions to follow-up device behavior, this study improves the understanding of hemodynamic factors associated with CNS shape modifications and suggests that simulation-based analysis may support future patient-specific treatment planning using exclusively pre-operative data.